OCCURRENCE, POPULATION DEVELOPMENT, INFESTATION AND DAMAGE CAUSED BY OLIVE FLY (BACTROCERA OLEA GMEL.) (DIPTERA: TEPHRITIDAE) IN OLIVE ORCHARDS OF MARDIN PROVINCE, TURKEY - M. Kaplan; Y. Bayram (Journal of Animal and Plant Sciences, 2020)
This study was conducted to determine the occurrence, population growth, infestation and damage caused by Olive fly in olive orchards of Mardin province during 2016-2017. Pheremone traps, yellow sticky traps and beat sheet sampling were used to monitor population development and other parameters. It was observed that the first adults emerged at the end of July or beginning of August and the pest continued emerging until end of November. The pest occurred in 42.5% of the monitored orchards, with very low infestation (1.7-3.81%) and damage rate (2.4%-4.2%). The highest damage and infestation were recorded in Derik-1 area, while the lowest damage and infestation was noted in Dara orchard. The peak population development was observed during October in all orchards. Although population development varied in different years depending on temperature and humidity, Olive fly constitutes two peaks per year. The first peak appeared in September, while the latter in October. Overall, the pest had low population pressure in the monitored orchards in Mardin province. However, September and October are very critical for producers; therefore, management strategies should be opted against the pest during these months. Since olive fruits enter maturity phases during this period, these are susceptible to oviposition by the pest. Pest population could be significantly high, unless pest controlled during September and October. Yellow sticky traps combined with pheromone traps were 2-3 times more effective than Mcphail traps combined with 2% diammonium phosphate. Therefore, yellow sticky traps combined with pheromone traps will be beneficial against the pest as an effective biotechnical control strategy.
Keywords: Olive; Olive fly; Bactrocera oleae; Infestation; Occurrence; Damage; Mardin province; Turkey